Developing cultural humility embracing race, privilege and power - Gallardo, Miguel E. (SAGE, 2014)
'Developing Cultural Humility' offers a unique look into the journeys of psychologists striving towards an integration of multiculturalism in their personal and professional lives. Contributing authors - representing a mix of 'cultural backgrounds' but stereotypically identified as 'White' - engage in thoughtful dialogue with psychologists from underrepresented communities who are identified as established and respected individuals within the multicultural field